The effects of dorzolamide on choroidal and retinal perfusion in non-exudative age related macular degeneration. Issue 6 (1st June 2003) - Harris, A; Ciulla, T A; Pratt, L M; Rechtman, E; Kagemann, L; Piper, H C; Garzozi, H J
Abstract : Aim: To comprehensively evaluate the effects of dorzolamide on the choroidal and retinal circulation in patients with age related macular degeneration (AMD). Methods: In this randomised, double masked, parallel study, 36 non-exudative AMD patients were randomised in a 2 to 1 fashion to placebo versus topical dorzolamide and underwent assessment of their choroidal and retinal circulation. Scanning laser ophthalmoscope indocyanine green angiograms (ICGA) were analysed by a new area dilution analysis technique. Four areas in the perifoveal region and two areas in the temporal peripapillary region were evaluated by plotting intensity of fluorescence of each area over time. The means of the choroidal filling times and the heterogeneity of the filling times were assessed. Scanning laser ophthalmoscope fluorescein angiography (FA) was evaluated for retinal arteriovenous passage (AVP) times by plotting intensity of fluorescence of retinal vessels over time. Assessment was performed at baseline and at 4 months. Results: Compared to placebo, AMD patients treated with dorzolamide showed a significantly increased rapidity of choroidal filling in the superior and inferior peripapillary regions (p=0.007, p=0.02, respectively). No significant difference in choroidal filling times was found in any of the perifoveal areas (p=0.9). Also, on FA assessment, treatment with dorzolamide showed no statistical differences in AVP times (p=0.19). Conclusions: Dorzolamide may increase peripapillary choroidal perfusion in non-exudative AMD patients. Further studies are merited.